1991
DOI: 10.1295/polymj.23.1325
|View full text |Cite
|
Sign up to set email alerts
|

Helix-Sense Inversion in Polyaspartates

Abstract: ABSTRACT:Solid-state irreversible inversion of helix sense of poly(/J-(p-chlorobenzyl) Laspartate) and poly(/J-(p-methylbenzyl) L-aspartate) was investigated by employing circular dichroism, infrared absorption, and X-ray diffraction techniques. The molecular conformation was the right-handed ()(-helix ((l(R) in the as-cast film prepared from the solution in chloroform. Heat treatment caused the transition from (l(R to the left-handed w-helix (wd. The crystal structure of the wL forms was monoclinic (not tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…11 PBLA and its derivatives carrying a methyl or chloro substituent at the para position of the terminal aromatic residue are known to exhibit a screw-sense inversion from the righthanded R-helix to the left-handed ω-helix at around 150 °C. [12][13][14] Recently, one of the present authors has reported a helix-helix transformation of poly(L-aspartic acid ester) with long n-alkyl side chains (R ) (CH 2 ) n H, n ) 12-18) at around 150 °C. 15 In all these examples, however, the transition is observed only on heating and the high-temperature form remains unchanged on cooling.…”
Section: Introductionmentioning
confidence: 88%
“…11 PBLA and its derivatives carrying a methyl or chloro substituent at the para position of the terminal aromatic residue are known to exhibit a screw-sense inversion from the righthanded R-helix to the left-handed ω-helix at around 150 °C. [12][13][14] Recently, one of the present authors has reported a helix-helix transformation of poly(L-aspartic acid ester) with long n-alkyl side chains (R ) (CH 2 ) n H, n ) 12-18) at around 150 °C. 15 In all these examples, however, the transition is observed only on heating and the high-temperature form remains unchanged on cooling.…”
Section: Introductionmentioning
confidence: 88%
“…In 1991, Sasaki et al described the solid-state inversion of helicity in thin films of poly(β-(pchlorobenzyl)-L-aspartate) and poly(β-(p-methylbenzyl)-L-aspartate) prepared by drop casting from a CHCl 3 solution: an inversion of the ECD band at 230 nm was observed for both samples after thermal annealing at 180−220 °C, thus revealing an irreversible transition from a right-handed α-helix to a lefthanded ω-helix (further confirmed by X-ray diffraction analysis). 498 Cho and co-workers reported a comparison of the ECD properties for drop-casted films and Langmuir− Blodgett layers of poly(γ-benzyl-L-glutamate)/poly(propylene oxide) 499 and of poly(γ-benzyl-L-glutamate)/poly(ethylene oxide)/poly(γ-benzyl-L-glutamate) 500 block copolymers, show- ing different degrees of orientation depending on the length of polyether blocks. Structural properties of drop-casted thin films of poly(L-glutamic acid) derivatives with aromatic 501 and azobenzene 502 groups as side-chain chromophores, as well as poly(L-glutamine)s bearing pyrene chromophores in the side chains, 503 have also been studied through ECD.…”
Section: Ecd In Thin Films Of π-Conjugated Oligomers and Polymersmentioning
confidence: 99%
“…Here, we will briefly discuss only oligo- and polypeptides with π-conjugated moieties in side chains, which have been investigated only more recently. In 1991, Sasaki et al described the solid-state inversion of helicity in thin films of poly­(β-( p -chlorobenzyl)- l -aspartate) and poly­(β-( p -methylbenzyl)- l -aspartate) prepared by drop casting from a CHCl 3 solution: an inversion of the ECD band at 230 nm was observed for both samples after thermal annealing at 180–220 °C, thus revealing an irreversible transition from a right-handed α-helix to a left-handed ω-helix (further confirmed by X-ray diffraction analysis) . Cho and co-workers reported a comparison of the ECD properties for drop-casted films and Langmuir–Blodgett layers of poly­(γ-benzyl- l -glutamate)/poly­(propylene oxide) and of poly­(γ-benzyl- l -glutamate)/poly­(ethylene oxide)/poly­(γ-benzyl- l -glutamate) block copolymers, showing different degrees of orientation depending on the length of polyether blocks.…”
Section: Ecd Properties In Thin Films Of π-Conjugated Systems: Litera...mentioning
confidence: 99%
“…Poly(β‐ p ‐chlorobenzyl L ‐aspartate) (PClBLA) is one of the well‐studied polyaspartate derivatives in both solution and the solid state 29–35. The chemical structure of PClBLA differs from those of PBLA and PPLA only at the terminal of the relatively long side chain.…”
Section: Introductionmentioning
confidence: 99%